Orthostatic Dysregulation during Postural Change on the Dental Chair and Intraoperative Monitoring by Heart Rate Variability Analysis - Yukihiro Momota; Shigemasa Tomioka; Mayuko Furukita; Kenji Fujisawa; Hideyuki Takano; Masayuki Azuma (Case Reports in Dentistry)
This is the first case report of orthostatic dysregulation (OD) manifested during postural change on the dental chair and intraoperatively monitored by heart rate variability (HRV) analysis. OD-associated autonomic dysfunction is induced by postural changes and easily leads to disturbance in circulatory dynamics; however, most dental practices have not yet realized the importance of managing OD. We measured autonomic activity in a patient with OD during dental therapy and assessed the clinical significance of HRV analysis for OD. The patient was a 17-year-old Japanese female. She was diagnosed with impacted wisdom teeth and had no previous history of a distinct systemic disease. A surgical procedure to extract the teeth was safely performed under both local anesthesia and sedation with nitrous oxide and midazolam. After the surgery, her postural change to sitting induced orthostatic hypotension. HRV variables showed parasympathetic dominance due to the upright position. Subsequently, her posture was returned to supine, and atropine sulfate administration for the immediate treatment of OD returned her blood pressure to normal levels. HRV variables showed relative sympathetic dominance due to an atropine-derived parasympathetic blockade. HRV analysis revealed OD-associated autonomic dysfunction and should become a standard tool for safe and secure dental management of OD.